KEPASTIAN HUKUM WAKAF UANG DI INDONESIA - Utama, Sofyan Mei (Jurnal Wawasan Yuridika, 2012)
Waqaf, property donated for religious or community use which is known in the society is waqaf of land, or house. But, nowadays waqaf has been wider as can be seen in article 15 paragraph 3, Act No. 41 year 2004 on waqaf. Waqaf can be in the form of giving or donating movable objects, such as money, gold. Article 28 and 29 are the basis of the existence of law of money waqaf, so it has a legal certainty, and it can be applied in Indonesia according to syariah.Keywords: money waqaf, legal certainty, syariah.